KEBERPIHAKAN PROGRAM BUMI SEJUTA SAPI PEMERINTAH PROVINSI NTB TERHADAP PETERNAK SAPI - Zulkarnaen Zulkarnaen (SOCIETY, 2014)
West Nusa Tenggara provence is one of Caou producen which has landfor grows of cao are lagers enough. The capacity of cao are two millionsper a year. Which is ued just 34.79 percent. So that the government of WestNusa Tenggara provence want to make meat production trought BSS.There are two things are very good potencials are making famerdoingdifficult is: Control of cutting cows, from 20% to 5% in 2018; shippingrestrictions cows outside the region of 13,000 head into 8.500 tail. Thiscan result in a weak bargaining position of farmers become. Objective:to know the model applied marketing NTB provincial government afterthe BSS program; determine the economic impact of changes in incomebreeders seen breeder after BSS program. This study used a qualitativeapproach with descriptive exploratory method. Research conducted on12 groups of farmers in the district of Praya Timur. The analysis modelis the analysis Miles Huberman. Result: The model of post-programBSS livestock marketing is no different from previous models in whichfarmers are free to market their animals to the buyer with the provisionsof the beneficiaries of the program BSS livestock, livestock sales elseis to be done after the birth of at least two. Economic impact farmers/breeders seen from the movement of revenues, it turns BSS programcan have a positive impact (intended impact) to farmers.